ANALISIS KEBUTUHAN PEMBELAJARAN BERBASIS CLT SEBAGAI DASAR PENGEMBANGAN MODEL ENGLISH IMMERSIVE LEARNING DI SEKOLAH DASAR - Sirait, Albert; Hasratuddin; Retno Dwi Suyanti (JS (JURNAL SEKOLAH), 2026)
Abstract: This article presents a needs analysis study of Communicative Language Teaching (CLT)-based learning as a foundation for developing an English Immersive Learning model in elementary schools. The study employed a descriptive qualitative approach, involving five public elementary schools in Medan with 15 English teachers and 150 fourth-grade students as participants. Data were collected through observation, interviews, and questionnaires, then analyzed using Miles and Huberman's interactive model. The findings reveal that current English learning in elementary schools remains predominantly teacher-centered, lacking communicative activities that stimulate genuine language use. Students demonstrated high intrinsic motivation toward interactive and contextual learning experiences. These needs indicate the urgency of developing an English Immersive Learning model grounded in CLT principles to foster communicative competence from an early age. Keyword: Needs Analysis, CLT, English Immersive Learning, Elementary School, Communicative Competence Abstrak: Artikel ini menyajikan hasil analisis kebutuhan pembelajaran berbasis Communicative Language Teaching (CLT) sebagai dasar pengembangan model English Immersive Learning di sekolah dasar. Penelitian menggunakan pendekatan kualitatif deskriptif yang melibatkan lima sekolah dasar negeri di Kota Medan dengan 15 guru bahasa Inggris dan 150 murid kelas IV sebagai partisipan. Data dikumpulkan melalui observasi, wawancara, dan angket, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian mengungkapkan bahwa pembelajaran bahasa Inggris di sekolah dasar masih didominasi pendekatan teacher-centered dan minim aktivitas komunikatif yang mendorong penggunaan bahasa secara autentik. Murid menunjukkan motivasi intrinsik yang tinggi terhadap pengalaman belajar yang interaktif dan kontekstual. Temuan kebutuhan tersebut mengindikasikan urgensi pengembangan model English Immersive Learning berbasis CLT untuk menumbuhkan kompetensi komunikatif sejak usia dini. Kata Kunci: Analisis Kebutuhan, CLT, English Immersive Learning, Sekolah Dasar, Kompetensi Komunikatif